1995
DOI: 10.1530/eje.0.1330680
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of lung volumes and respiratory muscle strength in adult patients with growth hormone deficiency

Abstract: Little is known of the respiratory function in patients with growth hormone (GH) deficiency. The aim of the present study was to evaluate lung volumes and respiratory muscle strength in patients diagnosed as GH deficient in childhood. Ten patients diagnosed as GH deficient in childhood and ten healthy subjects entered the study. For each subject the evaluation of respiratory function followed the same standard approach, consisting of respiratory muscle strength assessment, recording of flow-volume curves, meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
2
10
1
Order By: Relevance
“…However, this is not the case in our patient as the plasma levels of thyroid hormones were within normal ranges with hormone substitution when he was diagnosed as respiratory failure. On the other hand, it is also reported that adult patients with GH deficiency showed moderate impairment of ventilatory function6 and that GH replacement therapy reversed that function 7. While it has been postulated that respiratory dysfunction in patients with GH deficiency might be due to weakened respiratory muscle strength and a reduction of lung volumes,7 there are no reports, to our knowledge, showing that GH deficiency resulted in severe respiratory failure as in our case.…”
Section: Discussionsupporting
confidence: 51%
“…However, this is not the case in our patient as the plasma levels of thyroid hormones were within normal ranges with hormone substitution when he was diagnosed as respiratory failure. On the other hand, it is also reported that adult patients with GH deficiency showed moderate impairment of ventilatory function6 and that GH replacement therapy reversed that function 7. While it has been postulated that respiratory dysfunction in patients with GH deficiency might be due to weakened respiratory muscle strength and a reduction of lung volumes,7 there are no reports, to our knowledge, showing that GH deficiency resulted in severe respiratory failure as in our case.…”
Section: Discussionsupporting
confidence: 51%
“…For instance, large lungs (Bartlett, 1971), upper airflow obstruction (Trotman-Dickenson et al, 1991), and narrowing of the small airways (Harrison et al, 1978) accompany GH excess, whereas a decrease in muscle strength and a reduction in the maximum inspiratory and expiratory pressure (Merola et al, 1995(Merola et al, , 1996 are associated with GH deficiency. The possibility that the lung is a target site for GH action is also indicated by the GH-induced production of superoxide by alveolar macrophages (Edwards et al, 1992), the GH-induced increase in circulating lung neutrophil activation during sepsis, and the accompanying increase in microvascular injury (Liu et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…The present patient also developed hypoxia and hypercapnia due to the markedly decreased VC. Adult patients with CPHD have been reported to show impairment of ventilatory function, and GH-replacement therapy can help restore it [4,11,12]. It has also been reported that GH-replacement therapy for GHD in adults results in increased maximal oxygen uptake, presumably due to increased respiratory muscle strength [13] and increased mean frequency of the surface electromyogram of the muscle fiber area in quadriceps [14].…”
Section: Discussionmentioning
confidence: 99%
“…Various hormone disturbances are therefore associated with impairment of respiratory muscle function [3]. For example, adult patients affected by childhood-onset GHD reportedly develop impaired ventilatory function due to reduced lung volumes and respiratory pressures, probably due to reductions in respiratory muscle strength [4]. In addition, GH is known to play a role in stimulating the glomerular filtration rate (GFR) [5,6], and GFR is decreased in patients with GHD [7].…”
Section: Introductionmentioning
confidence: 99%